2006
DOI: 10.1016/j.rmed.2006.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to pulmonary rehabilitation: A qualitative study

Abstract: This study has shown that the referring doctor plays a key role in the uptake of PR programmes. It suggests that a positive approach by doctors could increase the level of adherence to PR. Recognition and support in the area of social support for those living alone may also increase adherence. These simple, cost effective approaches may encourage more patients with COPD to participate in a therapeutic intervention which now has a strong evidence base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(185 citation statements)
references
References 21 publications
12
164
1
6
Order By: Relevance
“…The findings showed that the group itself was very important for some of the participants in terms of sharing experiences with others, as are also described in other studies from hospital settings (Petersson et al, 2000;Gustafsson et al, 2004;Monninkhof et al, 2004;Barlow et al, 2005;Clark et al, 2005;Arnold et al, 2006;Kanervisto et al, 2007;Wilson et al, 2007;Halding et al, 2010). The present findings are similar to other findings where persons with other chronic diseases have told that the group promotes a collective identity and sense of belonging (Clark et al, 2005;Halding et al, 2010) and that participants learned together how to manage the disease (Petersson et al, 2000;Barlow et al, 2005;Clark et al, 2005;Arnold et al, 2006;Halding et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings showed that the group itself was very important for some of the participants in terms of sharing experiences with others, as are also described in other studies from hospital settings (Petersson et al, 2000;Gustafsson et al, 2004;Monninkhof et al, 2004;Barlow et al, 2005;Clark et al, 2005;Arnold et al, 2006;Kanervisto et al, 2007;Wilson et al, 2007;Halding et al, 2010). The present findings are similar to other findings where persons with other chronic diseases have told that the group promotes a collective identity and sense of belonging (Clark et al, 2005;Halding et al, 2010) and that participants learned together how to manage the disease (Petersson et al, 2000;Barlow et al, 2005;Clark et al, 2005;Arnold et al, 2006;Halding et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…The present findings are similar to other findings where persons with other chronic diseases have told that the group promotes a collective identity and sense of belonging (Clark et al, 2005;Halding et al, 2010) and that participants learned together how to manage the disease (Petersson et al, 2000;Barlow et al, 2005;Clark et al, 2005;Arnold et al, 2006;Halding et al, 2010). As in another study, they felt that they had regained control over life and obtained a new identity, that of living with COPD (Halding et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Having a specific COPD class means participants are empathetic towards others with symptoms of breathlessness and sputum production, and so are less self-conscious about their bodies' unpredictable behaviours (Gullick, 2008, Arnold et al, 2006. Under supervision, people become more comfortable exerting their body and are less likely to become panicked by exertional dyspnoea (Williams et al, 2010).…”
Section: The Impact Of Pulmonary Rehabilitation For the Patient And Fmentioning
confidence: 99%
“…In this sense, the absence of psychosocial measures may also have been relevant. However, it should be noted that the number of assessed patients was higher than previously used in similar studies on adherence to PR 17,18 . Another important limitation is the non-inclusion of more complex measures of lung function, such as static lung volumes and diffusing capacity, thus not allowing a better phenotypic characterization of the participants 35 .…”
Section: Discussionmentioning
confidence: 77%
“…Adherence to the PR was defined as the participant's ability to complete the proposed program, with at least 80% attendance of sessions [16][17][18] . If the participant withdrew from the PR before the end of the proposed period, he/she was asked to state the reasons for withdrawal.…”
Section: Adherence To Prmentioning
confidence: 99%